THE BIOTECHNOLOGY AND THE BIOETHICAL CARRIED FOR HEALTH - Marilene Mangini Correia; Verônica Mello de Azevedo Mazza; Mariluci Alves Maftum (Universidade Federal de Goias, 2004)
One is about a reflection on some recurrent controversial subjects of the present time of theadvances of the biotechnology, as the attended reproduction, the cloning human being, the production oftransgênicos products and others that not rare are part of day-by-day of the health professionals. Subjects forwhich answers in Laws and Professional Codes of Ethics are not found, with also not have a consensus in aplural society, some time that involve divergent beliefs and cultural values. However the health professionals thathave in the exercise of the profession the responsibility to clarify even though to safeguard the right of the patientin the taking of decisions or the times have the paper to decide and to make choices for it, becomes necessarythis knowledge as base of one practical professional, in which the respect and dignity human being is the mark ofthe quality.